Today's moral issues (McGraw-Hill, 2013)
Today’s Moral Issues combines theoretical and practical readings on four general themes: first principles, liberty, rights and responsibilities, and justice and equality. The theoretical readings from classical philosophy, which appear at the beginning of each of the four parts of the book, are closely related to the contemporary readings that follow, which cover “hot button” issues of interest to today’s students